Biodiversity of fungi in hot desert sands. Issue 1 (5th March 2018) - Murgia, Manuela; Fiamma, Maura; Barac, Aleksandra; Deligios, Massimo; Mazzarello, Vittorio; Paglietti, Bianca; Cappuccinelli, Pietro; Al‐Qahtani, Ahmed; Squartini, Andrea; Rubino, Salvatore; Al‐Ahdal, Mohammed N.
Abstract: The fungal community of six sand samples from Saudi Arabia and Jordan deserts was characterized by culture‐independent analysis via next generation sequencing of the 18S rRNA genes and by culture‐dependent methods followed by sequencing of internal transcribed spacer (ITS) region. By 18S sequencing were identified from 163 to 507 OTUs per sample, with a percentage of fungi ranging from 3.5% to 82.7%. The identified fungal Phyla were Ascomycota, Basal fungi, and Basidiomycota and the most abundant detected classes were Dothideomycetes, Pezizomycetes, and Sordariomycetes. A total of 11 colonies of filamentous fungi were isolated and cultured from six samples, and the ITS sequencing pointed toward five different species of the class Sordariomycetes, belonging to genera Fusarium ( F . redolens, F . solani, F . equiseti ), Chaetomium ( C. madrasense ), and Albifimbria ( A. terrestris ). The results of this study show an unexpectedly large fungal biodiversity in the Middle East desert sand and their possible role and implications on human health. Abstract : Results from this study evidence an unexpectedly large fungal biodiversity in the Middle East desert sand, predominantly consisting of fungi adaptive for survival in the extreme environmental conditions prevailing in deserts, indicating the robustness and endurance of microorganisms. This study suggests that desert sand and plants may be a rich source of fungi, tolerant to extreme environmental conditions that could be examined for plant growth promotion activity in agriculture. Moreover, this study might be helpful to resolve the strategies adopted by microbes in response to extreme conditions to defeat draining by induction of various types of solutes. Furthermore physicochemical analyses of sand could uncover a more complete screenplay of the abiotic factors and fungal interplay conditions existing in the desert areas.